2022
DOI: 10.1177/17449871221079175
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ lived experiences of caring for patients with COVID-19: a phenomenological study

Abstract: Background COVID-19 is an infectious disease caused by a novel Coronavirus which transmits from person to person throughout the world. This study aimed to explore the lived experiences of nurses’ caring for patients with COVID-2019 in the context of the healthcare system of Iran. Methods This is a phenomenological study with 13 participant nurses (6 men and 7 women) who were caring for COVID-19 patients in one of the university hospitals in Southeast of Iran. Qualitative data were analysed by the seven steps o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The fundamental structure of the phenomenon was then described. The last step was to validate the findings using feedback from participants on the analyses [25]. At first, the data revealed six themes and four sub-themes.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental structure of the phenomenon was then described. The last step was to validate the findings using feedback from participants on the analyses [25]. At first, the data revealed six themes and four sub-themes.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses felt a conflict between their professional duties as a nurse and their self-protection and the protection of their families from the disease. 20 In a qualitative study, Liu et al also expressed the view of nurses as a sense of full responsibility for patient recovery and as a duty; the health team strives to provide the best care for patients and return them to daily activities of life. 10 Kim’s study also showed that nurses who participated in the care of patients with MERS, had a stronger sense of responsibility and professional ethics and mainly did not raise physical and psychological injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The specialist consolidated the comprehensive depiction down to a short, broader explanation that caught those viewpoints considered to be crucial for the construction of the peculiarity. The scientist returned the central design articulation to all members to find out if it captured their encounters (Heydarikhayat et al 2022 ). Three themes and five sub-themes emerged from the data.…”
Section: Methodsmentioning
confidence: 99%